Participles and adverbial participles in teaching Russian as a foreign language - Nagaitseva, N. I.; Romanov, Yu. O. (ВД "Гельветика", 2020)
This article considers participles and adverbial participles, the extremely complex and specific phenomena, though scarcely highlighted in programs on teaching Russian as a foreign language (RFL). It is quite clear that an immersion in participles and adverbial participles cannot be superficial; they require non-standard approaches to their presentation. In RFL teaching, it is important to follow the theoretical foundations acccording to which participles and adverbial participles are understood as special hybrid parts of speech that synthesize some of semantic, morphological, and syntactic features of a verb and adjective (participles), verb and adverb (adverbial participles). The features of adverbial participles to be taken into account are followings: “second predicate” role, i.e. ability to express additional action of the same subject; irregular way of formation; influence of verbal aspectual and temporal factors exerted on the grammatical meaning; adverbial participial phrase peculiarities; obsolete forms of perfect adverbial participles occasional adverbial participle formation. The peculiarities of participles to be placed the emphasis on are: they receive the category of transitivity / intransitivity and voice meanings from the productive verbs (but the forms for expressing voices (active and passive) in verbs and participles are different), and the features expressed by participles are temporary in contrast to the permanent features expressed by adjectives; there are full and short forms of participles; participle clauses (participles with dependent words) are easily replaced by synonymous definitive subordinate clauses with connective word который; in a system of participles, loss of affiliation with verb may occur; occasional participles, often present in literary texts, require special learners’ attention. Thus, adverbial participles and participles are to be considered living and promising parts of speech of modern Russian language widely used both in artistic works and in the language of science.

У статті розглянуто дієприкметники та дієприслівники – надзвичайно складні та специфічні явища, недостатньо висвітлені у програмах викладання російської мови як іноземної (РЯІ). Цілком зрозуміло, що занурення у вивчення дієприкметників та дієприслівників не може бути поверхневим; вони вимагають нестандартних підхо- дів до їхнього викладання. У викладанні РЯІ важливо дотримуватися теоретичних уявлень, згідно з якими дієприкметники та дієприслівни- ки вважають особливими гібридними частинами мови, що синтезують деякі семантичні, морфологічні та синтаксичні особливості дієслова та прикметника (дієприкметники) і дієслова та прислівника (дієприслівники). Особливості дієприслівників, які слід враховувати під час викладання, є такими: роль дієприслівника як «другого предиката», тобто його здатність відбивати додаткові дії того самого підмета; нерегулярний спосіб формування; вплив дієслівних видових та часових факторів на граматичне значення; особливості дієприслівникових зворотів; застарілі форми дієприслівників доконаного виду; утворення оказіональних дієприслівників. Особливості дієприкметників, на які слід акцентувати увагу, полягають у тому, що: вони отримують категорію транзитивності / інтранзитивності та станові значення від продуктивних дієслів (але форми вираження стану (активного та пасивного) у дієсловах та дієприкметників різні), і ознаки, виражені дієприкметниками, є тимчасовими, на відміну від постійних ознак, виражених прикметниками; існують повні та короткі форми дієприкметників; дієприкметникові звороти (дієприкметники із залежними словами) легко замінюються синонімічними підрядними реченнями зі сполучним словом который; у системі дієприкметників може статися втрата приналежності до дієслова; оказіональні дієприкметники, що часто присутні в літературних текстах, потребують особливої уваги. Таким чином, дієприслівники та дієприкметники слід вважати живими та перспективними частинами сучасної російської мови, що широко використовуються як у художніх творах, так і в науковому мовленні.
Дієприкметники і дієприслівники у викладанні російської мови як іноземної
Keywords: participles; adverbial participles; parts of speech; foreign language; learning of language; teaching of language; дієприкметники; дієприслівники; частини мови; російська мова; іноземна мова; вивчення мови; викладання мови